2022
DOI: 10.1039/d2lc00597b
|View full text |Cite
|
Sign up to set email alerts
|

Enabling perfusion through multicellular tumor spheroids promoting lumenization in a vascularized cancer model

Abstract: Tumor is composed of heterogeneous cell population, which is known as tumor stroma. In particular, blood vessels have an indispensable role in the tumor microenvironment acting as a key player...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Park et al. ( 31 ) demonstrate the use of tri-culture spheroid comprising tumor cells, ECs, and fibroblasts. The tri-culture spheroid has a more robust intratumoral vasculature and connects better with the external microvasculature network.…”
Section: Vascularization Strategiesmentioning
confidence: 99%
“…Park et al. ( 31 ) demonstrate the use of tri-culture spheroid comprising tumor cells, ECs, and fibroblasts. The tri-culture spheroid has a more robust intratumoral vasculature and connects better with the external microvasculature network.…”
Section: Vascularization Strategiesmentioning
confidence: 99%
“…Owing to the independent compartments in microfluidics, various parameters, such as mechanical forces, tissue interface orientation, cell types and localization, and biochemical gradients, can be precisely controlled. Microfluidics can introduce different cell types and circulating systems (such as blood or lymphatic vessels) into the 3D structure, thereby providing an ideal platform for TME or cancer-immunity cycle (CIC) research, as well as for drug testing and discovery [113][114][115][116]. Moreover, microfluidic devices require a very small volume of samples and reagents for analysis; therefore, they have great potential for high-throughput screening [117,118].…”
Section: Vessel-based Dynamic 3d Modelsmentioning
confidence: 99%
“…Microfluidic chips can be used to evaluate antimetastatic therapies and investigate the mechanisms underlying vasculature-driven invasive tumor phenotypes.Bai et al [119] embedded bladder cancer cell aggregates in a collagen scaffold adjacent to an endothelial cell channel to screen therapeutic epithelial-mesenchymal transition blocking agents. The efficacy of each drug was evaluated based on its Reproduced from [116] with permission from the Royal Society of Chemistry. (iii) Fluorescence image showing CTL clustering on the spheroid during first fragmentation event.…”
Section: Vessel-based Dynamic 3d Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the continuous development of microfabrication technology, microfluidic tumor–vessel chips not only help to precisely arrange the spatial distribution of cellular components in vitro but can also apply biomechanical and biochemical stimuli, including blood flow and growth factor gradient, thereby reproducing the interaction between the heterotypic tumor and TME with high fidelity. For example, Haase et al reported an on-chip 3D-vascularized tumor model for drug examination in a TME within a large bed of perfusable vasculature. , They demonstrated that the dose-dependent effect of anticancer drugs on tumor activity was significantly affected by the form of vascular infusion administration. Meanwhile, great strides have also been made in the field of biomaterials. , As a representative biomaterial, GelMA has been widely used in the regenerative medicine field for 3D cell culture. , Various organ models have been successfully established in GelMA, which demonstrate its good biocompatibility. ,, Antunes et al reported an in-air production of tumor spheroid-laden GelMA microgel to expedite drug screening, where GelMA was involved as tumor–ECM .…”
Section: Introductionmentioning
confidence: 99%